Blood selenium concentrations and glutathione peroxidase activity. Issue 3 (March 1989) - Lloyd, B; Robson, E; Smith, I; Clayton, B E
Abstract : Selenium concentrations in children and teenagers without a metabolic disorder eating normal diets (group 1), and young patients with classical phenylketonuria and milder forms of hyperphenylalaninaemia being treated with a diet low in natural protein (group 2) were investigated. There was a strong correlation between blood selenium concentration and age in children in group 1 up to 10 years of age. Blood selenium concentrations and glutathione peroxidase activities were significantly lower in the patients who were receiving diets containing reduced amounts of natural protein, and the differences were more than would be expected for age. When the concentrations of selenium in blood from groups 1 and 2 were compared with glutathione peroxidase activity, a strong association was found when blood selenium concentrations were below 1.26 mumol/l. Reduction in glutathione peroxidase activity may be harmful in the long term, and the addition of selenium to therapeutic diets is recommended.